Were there philosophy in ancient Sparta? – 2 - Panafidin, Igor (Actual Problems of Mind, 2017)
By analysing the sources from the ancient authors the authors attempts to reconstruct the cultural, in particular philosophical legacy of spartans. It is claimed that already in works by Plato and Plutarch one can find an ambivalent position concerning the possibility of philosophy in ancient Sparta, and this discussion remains relevant to the present days.